FDI and Regional Economy in China - Kong, Decong; Štěrbová, Ludmila, 1957-; Mazánková, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This paper address the current state of FDI in China and the impact of FDI on the regional economy.Nowadays, China's development speed has far surpassed other developing countries, and it has surpassed the U.S. to become the country with the largest FDI inflows in 2020. The rapid development of FDI has played a key role. At the same time, the inflow of FDI has also affected the development of regional economic in China to a certain extent. The paper concludes through the data analysis that FDI has not had a direct impact on the regional economy in the past ten years. However, The development of Special Economic Zones and FDI are inextricably linked. The establishment of Special Economic Zones has greatly attracted the inflow of FDI, which has provided a rapid rise for development of China.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses